Development of STEM Based-Integrated Electrochemistry Enrichment Book: An Analysis Review - Triayuni, Tami; Irwandi, Dedi; Muslim, Buchori (Gemilang Maju Publikasi Ilmiah (GMPI), 2023)
The research aimed to develop a STEM-based chemistry enrichment book on electrochemistry and find out the students' responses to the book. This development process uses a mixed method Cresswell version; qualitative approach for the development stage using text analysis and quantitative method for data statistics using data analysis. An enrichment book indicator is generated, which has been integrated with each STEM component to become a reference for developing an enrichment book. Then, a STEM-based chemical enrichment book was made on electrochemical materials. It was reviewed by expert validation of media materials: four chemistry education lecturers and one chemistry teacher. The average percentage from enrichment book validation results for each aspect of eligibility were: content, presentation, language, and graphics. Each has a value of 98.5%, 87.5%, 100%, and 100%. The final enrichment book product was tested on 37 students at one of the senior high schools in Indonesia. The student's response test results were 81.34%, including the proper category in a very good predicate. The product of this study result was proven to have a positive response that can be used in chemistry learning. It can be used as teaching material for schools and also can support STEM education in Indonesia.